Non-native species in the north Gulf of Aqaba (Red Sea) revealed from environmental DNA - Fernandez, Sara; Ardura, Alba; Georges, Oriane; Martinez, Jose L.; Suarez-Menendez, Marcos; Planes, Serge; Garcia-Vazquez, Eva (Frontiers in Marine Science, 2022)
The movement of species facilitated by anthropogenic activities represents a serious threat to marine diversity, especially for endemic species that may be outcompeted from non-indigenous newcomers. In this study we have analyzed communities inhabiting the Gulf of Aqaba (north Red Sea) employing environmental DNA (eDNA) metabarcoding. That gulf is especially rich in species and population endemism. We have detected a number of non-indigenous species (NIS) representing 36% of the total number of species found from eDNA. A significantly higher proportion of non-native than of native primary producers suggests that functional diversity could be altered if non-indigenous species thrive there. We discuss maritime traffic as a main factor that favors the NIS found in this study, and emphasize the importance of the control of these species that may threaten the rich endemic biota of the Red Sea.